AGE, PERIOD, AND COHORT EFFECTS ON DEATH PENALTY ATTITUDES IN THE UNITED STATES, 1974–20141. Issue 4 (4th November 2017) - ANDERSON, AMY L.; LYTLE, ROBERT; SCHWADEL, PHILIP
Abstract: In this article, we further the understanding of both changes in public opinion on capital punishment in the United States and changes in the factors associated with public opinion on the death penalty. Support for the death penalty may be motivated by events happening during specific time periods, and it can vary across birth cohorts as a result of cohort‐specific socialization processes, demographic changes, and formative events that are specific to each generation. An explication of the sources of and variation in death penalty attitudes over time would benefit from the accounting for the age of the respondent, the year of the survey response, and the birth cohort of the respondent. We improve on previous research by using multiple approaches including hierarchical age–period–cohort models and data from the General Social Survey (N = 41, 474) to examine changes in death penalty attitudes over time and across birth cohorts. The results showed curvilinear age effects, strong period effects, and weak cohort effects on death penalty support. The violent crime rate explained much of the variation in support for the death penalty across periods. The examination of subgroup differences suggests that support for the death penalty is becoming concentrated among Whites, Protestants, and Republicans.